2022
DOI: 10.3389/fonc.2022.1032115
|View full text |Cite
|
Sign up to set email alerts
|

Use of radiomics containing an effective peritumoral area to predict early recurrence of solitary hepatocellular carcinoma ≤5 cm in diameter

Abstract: BackgroundHepatocellular carcinoma (HCC) is the sixth leading type of cancer worldwide. We aimed to develop a preoperative predictive model of the risk of early tumor recurrence after HCC treatment based on radiomic features of the peritumoral region and evaluate the performance of this model against postoperative pathology.MethodOur model was developed using a retrospective analysis of imaging and clinicopathological data of 175 patients with an isolated HCC ≤5 cm in diameter; 117 patients were used for model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Previous studies have reported that radiomics analysis of intratumoral combined 3 mm, 5 mm, and 10 mm peritumoral regions can provide valuable information for prognosis prediction in HCC [ 18 , 19 , 30 , 39 , 40 ]. In addition, according to the practice guidelines for the pathological diagnosis of primary liver cancer (2015 update) [ 41 ], the liver tissues within 10 mm surrounding the tumor are defined as the adjacent areas around the cancer, where the probability of MVI is high.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported that radiomics analysis of intratumoral combined 3 mm, 5 mm, and 10 mm peritumoral regions can provide valuable information for prognosis prediction in HCC [ 18 , 19 , 30 , 39 , 40 ]. In addition, according to the practice guidelines for the pathological diagnosis of primary liver cancer (2015 update) [ 41 ], the liver tissues within 10 mm surrounding the tumor are defined as the adjacent areas around the cancer, where the probability of MVI is high.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, T-PTR radiomics models demonstrated better predictive performance compared with the TR radiomics model, which indicated that peritumoral radiomics might potentially enhance the ability of intratumoral radiomics for TACE response prediction. This might be interpreted that arterial peritumoral enhancement and irregular margin presented in the peritumoral area are independent predictors of prognosis in HCC patients [ 18 , 19 ]. Chen et al [ 30 ] found that intratumoral and peritumoral (5 mm, 10 mm, and 20 mm) radiomics models based on contrast-enhanced CT images performed better than the intratumoral radiomics model in predicting the first TACE response with the AUCs of 0.790, 0.810, 0.750, and 0.720, respectively, which was consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have included the peritumoral range for ROI analyses, gradually recognizing the importance of this region for tumor radiomics ROI ( 17 - 19 ). Nevertheless, the choice of the peritumoral ROI range for predicting ER of HCC remains controversial ( 20 , 21 ), and the optimal peritumoral ROI range needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%